Characterization of innate immune viral sensors in patients following allogeneic hematopoietic stem cell transplantation. Issue 2 (February 2018) - Caddy, Sarah L; Wang, Meng; Krishnamurthy, Pramila; Uttenthal, Benjamin; Chandra, Anita; Crawley, Charles; James, Leo C
Viral infection is a major cause of morbidity and mortality following allogeneic hematopoietic stem cell transplant (HSCT), with up to one in four deaths directly linked to viral disease. Whilst awaiting lymphocyte reconstitution post-HSCT, the innate antiviral immune response is the first line of defense against invading viruses. Several novel innate viral-sensing pathways have recently been characterized, but their physiological importance in humans is poorly understood. We analyzed a panel of innate viral-sensor genes in HSCT patients, and assessed whether differences in innate antiviral responses could account for variation in susceptibility to viral infections. Expression levels of innate viral sensors in HSCT patients with active viral infections, HSCT patients without active infections and healthy volunteers were highly homogenous. Although IFN-α expression was up-regulated in actively infected patients relative to controls, a corresponding up-regulation of innate viral sensor expression was not observed. IFN-α stimulation of patient PBMCs in vitro showed intact IFN-α signaling, but actively infected patients' PBMCs had reduced up-regulation of innate viral sensors. We show that the aberrant IFN-α responses in HSCT patients were not due to calcineurin inhibition. Our data therefore raises the possibility of an intrinsic defect in innate viral sensor up-regulation in HSCT patients following viral infection.